2020
DOI: 10.1097/pts.0000000000000748
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Rapid Response Teams to Reduce Failure to Rescue Events: A Systematic Review

Abstract: Overview of the 100,000 Lives Campaign "The names of the patients whose lives we save can never be known. Our contribution will be what did not happen to them. And, though they are unknown, we will know that mothers and fathers are at graduations and weddings they would have missed, and that grandchildren will know grandparents they might never have known, and holidays will be taken, and work completed, and books read, and symphonies heard, and gardens tended that, without our work, would never have been."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 21 publications
0
45
0
2
Order By: Relevance
“…In a study that measured the outcomes after the implementation of a rapid response system on a large healthcare jurisdiction, it was found that cardiopulmonary arrests, and related deaths, mortality and FTR decreased but at the same rate as before the implementation; however, the mortality in the low-mortality diagnostic-related group subpopulation decreased significantly. Other articles also report that RRTs have reduced hospital mortality, unplanned ICU transfers and unexpected cardiac arrests [19,27,46,47].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study that measured the outcomes after the implementation of a rapid response system on a large healthcare jurisdiction, it was found that cardiopulmonary arrests, and related deaths, mortality and FTR decreased but at the same rate as before the implementation; however, the mortality in the low-mortality diagnostic-related group subpopulation decreased significantly. Other articles also report that RRTs have reduced hospital mortality, unplanned ICU transfers and unexpected cardiac arrests [19,27,46,47].…”
Section: Resultsmentioning
confidence: 99%
“…Rapid response teams and medical emergency teams have become the standard approach to the efferent arm, becoming more prevalent in hospital systems overtime [19]. Their constitution may vary in different institutions, but they are typically multidisciplinary and comprise a critical care physician, a critical care nurse and a respiratory therapist at minimum [8,46]. Evidence also shows that intensivists used on rapid response teams are predictors of high performance and may improve FTR [8,10].…”
Section: Efferent Limbmentioning
confidence: 99%
“…Many hospitals operate rapid response teams (RRTs), which use uses medical alert systems to respond quickly to such adverse events. There is evidence of decreased mortality and non-ICU cardiac arrest rates with the use of RRTs; however, the effects of RRTs on ICU transfer rates are equivocal [ 7 ]. Several risk scoring systems are used to identify patients at high risk of serious adverse events including unexpected inpatient death.…”
Section: Introductionmentioning
confidence: 99%
“…These guidelines are a combination of 10 objective quantitative indicators ( ie , body temperature, systolic blood pressure, pulse rate, mean arterial pressure, shock index, respiration rate, peripheral oxygen saturation, peripheral blood glucose, state of consciousness, and pain score), and 48 and 25 common complaints or symptoms seen in priority general patients and trauma patients, respectively. In addition, computer-aided patient triage software [ 4 ] was developed to identify patients in need of emergency care. Emergency patients were triaged according to disease severity and were classified as level I (fatal, red), level II (critical, orange), level III (emergency, yellow), level IV (not urgent, green), and level V (non-emergency, blue).…”
mentioning
confidence: 99%
“…This truly reflects the “emergency” of the ED. The rescue team shares some responsibilities with the Rapid Response team [ 4 ] in critical care medicine and can effectively respond to all kinds of emergencies. In a previous study, [ 5 ] emergency treatment and medical safety were improved by formulating standardized clinical management guidelines based on the best available evidence.…”
mentioning
confidence: 99%